2015
DOI: 10.1111/fwb.12565
|View full text |Cite
|
Sign up to set email alerts
|

Realised and predicted changes in the invertebrate benthos after restoration of connectivity to the floodplain of a large river

Abstract: 1. River–floodplain interactions (i.e. lateral connectivity) are a major driver of the structure and function of the biota in floodplain waterbodies. Therefore, the enhancement of lateral connectivity is a key focus of large river restoration. The Rhône River restoration project in France includes an array of floodplain habitats and restoration measures, offering opportunities to test the predictability of changes in taxon abundance after connectivity restoration. 2. Quantitative samples of benthic macroinvert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…Such an improvement is suggested by the increased range of the lateral connectivity index values after restoration mentioned in Castella et al (2015) and the corresponding higher beta diversity of macroinvertebrate assemblages across restored floodplain channels. In particular, pre-restoration data were available for 88% of the channels that were reconnected downstream but only 57% of channels that were reconnected at both ends.…”
Section: Between-channel (Time-averaged) Grain Size Conditions and Thmentioning
confidence: 94%
See 2 more Smart Citations
“…Such an improvement is suggested by the increased range of the lateral connectivity index values after restoration mentioned in Castella et al (2015) and the corresponding higher beta diversity of macroinvertebrate assemblages across restored floodplain channels. In particular, pre-restoration data were available for 88% of the channels that were reconnected downstream but only 57% of channels that were reconnected at both ends.…”
Section: Between-channel (Time-averaged) Grain Size Conditions and Thmentioning
confidence: 94%
“…Castella et al, 2015;Paillex et al, 2015) is strongly related to overflow frequency and shear stress (Fig. Castella et al, 2015;Paillex et al, 2015) is strongly related to overflow frequency and shear stress (Fig.…”
Section: Feedbacks On the Indirect Index Of Lateral Connectivitymentioning
confidence: 94%
See 1 more Smart Citation
“…Such models complement taxa-level models as those developed in another article in this Special Issue (Castella et al, 2015). Here, we develop community-level models to predict changes in alien and native macroinvertebrate communities after restoration and to investigate potential interactions between them.…”
Section: Introductionmentioning
confidence: 99%
“…Studies looking for main drivers of community changes in floodplains invariably found hydrological variables describing the connection, respectively the isolation from the main channel to be the most important factors (e.g., bacteria (Lew et al, 2016), phytoplankton (Grabowska et al, 2014), macrophytes (Keruzoré et al, 2013), macroinvertebrates (Castella et al, 2015;Paillex et al, 2007), and fish (Daufresne et al, 2015)). However, hydrological connections were often modified by anthropogenic interventions affecting floodplains and large rivers (e.g., Olivier et al, 2009a;Tockner and Stanford, 2002).…”
Section: Introductionmentioning
confidence: 99%